HNF1B nephropathy has a slow-progressive phenotype in childhood-with the exception of very early onset cases: results of the German Multicenter HNF1B Childhood Registry - Okorn, Christine; Goertz, Anne; Vester, Udo; Beck, Bodo B; Bergmann, Carsten; Habbig, Sandra; König, Jens; Konrad, Martin; Müller, Dominik; Oh, Jun; Ortiz-Brüchle, Nadina; Patzer, Ludwig; et al. (Pediatric nephrology (Berlin, Germany), 2019)
BACKGROUND: HNF1B gene mutations are an important cause of bilateral (cystic) dysplasia in children, complicated by chronic renal insufficiency. The clinical variability, the absence of genotype-phenotype correlations, and limited long-term data render counseling of affected families difficult. METHODS: Longitudinal data of 62 children probands with genetically proven HNF1B nephropathy was obtained in a multicenter approach. Genetic family cascade screening was performed in 30/62 cases. RESULTS: Eighty-seven percent of patients had bilateral dysplasia, 74% visible bilateral, and 16% unilateral renal cysts at the end of observation. Cyst development was non-progressive in 72% with a mean glomerular filtration rate (GFR) loss of - 0.33 ml/min/1.73m2 per year (± 8.9). In patients with an increase in cyst number, the annual GFR reduction was - 2.8 ml/min/1.73m2 (± 13.2), in the total cohort - 1.0 ml/min/1.73m2 (±10.3). A subset of HNF1B patients differs from this group and develops end stage renal disease (ESRD) at very early ages < 2 years. Hyperuricemia (37%) was a frequent finding at young age (median 1 year), whereas hypomagnesemia (24%), elevated liver enzymes (21%), and hyperglycemia (8%) showed an increased incidence in the teenaged child. Genetic analysis revealed no genotype-phenotype correlations but a significant parent-of-origin effect with a preponderance of 81% of maternal inheritance in dominant cases. CONCLUSIONS: In most children, HNF1B nephropathy has a non-progressive course of cyst development and a slow-progressive course of kidney function. A subgroup of patients developed ESRD at very young age < 2 years requiring special medical attention. The parent-of-origin effect suggests an influence of epigenetic modifiers in HNF1B disease.
Keywords: Kidney Failure, Chronic; novorozenec; Infant, Newborn; Registries; Infant; Humans; Cystic kidney disease; genetické asociační studie; kojenec; dítě; Disease Progression; registrace; Child; HNF1B; Female; Hepatocyte Nuclear Factor 1-beta; Hypomagnesemia; Phenotype; lidé; Germany; Německo; předškolní dítě; ženské pohlaví; chronické selhání ledvin; Genetic Association Studies; Male; GFR decline; hepatocytární jaderný faktor 1-beta; fenotyp; Adolescent; progrese nemoci; věk při počátku nemoci; mužské pohlaví; Age of Onset; Child, Preschool; MODY; Polycystic Kidney Diseases; mladiství; polycystická choroba ledvin